Enhancing high-school students' conceptual understanding of the linkages between the earth and trigonometry through an inquiry-based learning unit - Pimpalak Wongapiwatkul (2018)
In order to make the Earth, as represented by the globe and the map, more understandable to high-school student, an inquiry-based learning unit on " The Earth and Trigonometry" was developed to supplement the traditional presentation of the longitude, latitude, the great circle, the meridian and the dateline. Students from two schools participated in the learning unit as groups in which they asked and answered questions, discussed with groupmates and class. The teacher acted as the facilitator who guided the students to the objectives by scaffolding their learning with basic trigonometry and geometry that they had learned from previous exposures. The teacher also conducted debriefing at which students and teacher participated to achieve better outcome overall. Several pilot studies were conducted in other schools before the teacher arrived at the final instructional unit reported here. Students' conceptual understanding from pre-, post-tests, observation of their co-operation, their feedbacks to the attitudinal questionnaire were analyzed and the preceding version modified for better understanding of the geographical parameters above. It was found that the most difficult topic was the 3-D projection on the three orthogonal axes; x, y, z. However, using improved three-dimensional physical models and illustrations, better conceptual understanding to the longitude, latitude, the great circle and its distance was achieved. © Common Ground, Pimpalak Wongapiwatkul, Parames Laosinchai, Pintip Ruenwongsa, Bhinyo Panijpan.